Hematological Parameters Influencing the Thrombostat 4000 - Söhngen, Dietmar; Hatistein, Eckhard; Heyll, Axel; Meckenstock, Gerald; Wienen, Simone; Schneider, Wolfgang (Seminars in Thrombosis and Hemostasis, 1995)
The effects of platelet counts, hematocrit, and leukocyte counts were studied on the closure times of the Thrombostat 4000 (in-vitro bleeding time, IVBT). Closure times became longer with platelet counts <50 × 109/L; an inverse linear correlation could be established. Hematocrit was also inversely correlated with the closure time. At constant platelet counts a hematocrit of 55% yielded an immediate closure of the filter, while with a hematocrit <15% no closure times could be measured. At constant platelet counts and hematocrits, nomonuclear and polymorphonuclear leukocytes also influenced closure times; increased counts resulted in shorter closure times. Leukocytes from a patient with chronic myelocytic leukemia had the same effects.
Keywords: Thrombostat; platelets; leukocytes; hematocrit; bleeding time